USAGE OF FITNESS TECHNOLOGIES IN THE TRAINING PROCESS OF COMBAT SPORTS ATHLETES (Physical Culture and Sport: Scientific Perspective, 2024)
The aim of the research is to theoretically justify the use of fitness technologies in the training process of combat sports athletes. The study employed complementary theoretical research methods, including analysis and synthesis of scientific-methodical literature on the features of educational and training processes in combat sports, particularly the use of fitness technologies. The work is based on the analysis of scientific literature dedicated to improving the special endurance of mixed martial artists aged 18-21. The absence of a unified perspective on the application of innovative fitness training methods in this context was identified. A comparative analysis revealed the advantages of fighters utilizing innovative methods, recommending their implementation in other clubs. The structure and characteristics of competitive bouts in combat sports were explored, determining the tactical actions and their impact on coordination abilities. Experiments confirmed the effectiveness of methods for developing coordination abilities. Other studies highlighted the importance of planning pre-competition training and optimizing workouts for improving aerobic endurance. The methodology of strength training for young hand-to-hand combat athletes was examined, identifying variations of speed-strength exercises for physical development. Factors influencing the choice of sports specialization were investigated, emphasizing the significance of individual timelines to achieve qualification levels in martial arts. The value of training based on martial arts philosophy, aimed at enhancing individuals in spiritual, intellectual, and physical aspects, was emphasized. In conclusion, various methods for improving the special endurance of mixed martial artists were studied. Experiments validated the advantages of innovative fitness training in combat sports. The obtained data provide a foundation for the development of fitness technologies. Future research will focus on creating a game-based fitness technology for pankrationists.
Keywords: pankration; fitness; technology; training process; functional state